Intravenous Atropine Relieves Coronary Arterial Spasm and Hemodynamic Decompensation during Recovery after Exercise - Hung, Ming-Jui (2000)
A 66-year-old man developed right coronary arterial spasm and hemodynamic decompensation during the early recovery phase of a treadmill exercise test. The unstable condition was corrected immediately after intravenous administration of atropine. A subsequent coronary angiographic study revealed insignificant right coronary artery stenosis. The pathophysiology of this response may be related to rapid alterations in autonomic balance during recovery after exercise. To our knowledge, this is the 1st reported case in which atropine effected immediate reversal of coronary arterial spasm and hemodynamic decompensation that were induced by exercise, rather than by pharmacologic agents. Atropine might be an effective treatment in patients who experience exercise-induced coronary arterial spasm and hemodynamic decompensation, but further investigation is warranted.